A Comprehensive Public-Private Partnership Concept for Resources Sustainability from a Mega-Project Management Multi-Level Perspective - Aura, Christopher Mulanda; Hassan, Farida; Osore, Melckzedeck K; Musa, Safina; Morara, George; Uku, Jacqueline (International Journal of Management and Sustainability, 2016)
This paper outlines an effective and comprehensive public-private partnership approach that has the potential to enhance natural resource management (NRM) and improve access to essential community services (CS). The paper is based on the institutional and resource-dependency theories on the management of Kenya Coastal Development Project (KCDP) community development fund (Known in Swahili as Hazina ya Maendeleo ya Pwani, HMP), financed by Kenya Government through a loan from the World Bank at the Kenya coast. The HMP fund targets CS and NRM sub projects implemented by communities in the six coastal counties. To ensure sustainability of HMP financed sub projects, the framework involved strategic planning, system design, finance usage, implementation, and connection of theory and practice based on research and interpretation. KCDP data on HMP financed community projects implemented since 2013-2015 was used in the evaluation of project performance. Counties with enhanced security, and improved socio-economic status benefit the most in the project. The coastal communities were more willing-to-contribute towards implementation of CS than NRM projects due to consumptive nature attached to the former in the short term. Gender parity in the HMP participation occurred, attracting more women than men. By careful designation of the project management framework, sustainable management of natural resources and access to most immediate needs, considered crucial by coastal residents are highly likely to be met.